2005
DOI: 10.1063/1.2056581
|View full text |Cite
|
Sign up to set email alerts
|

Wave propagation in nonlinear left-handed transmission line media

Abstract: Using a one-dimensional system, we demonstrate a wide variety of wave propagation phenomena possible in nonlinear left-handed media. These include effective second-harmonic generation where the fundamental wave and the second-harmonic wave are badly mismatched. We also observe parametric instabilities accompanying intensive harmonic generation. © 2005 American Institute of Physics. ͓DOI: 10.1063/1.2056581͔Negative-refractive-index metamaterials, also known as left-handed ͑LH͒ media, first postulated by Veselag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 23 publications
3
50
0
1
Order By: Relevance
“…Some of these features have already been experimentally observed in nonlinear left-handed transmission lines which are model systems allowing for combining nonlinearity and anomalous dispersion [17,18,19]. Moreover, first results on harmonic generation in infrared were reported in Ref.…”
mentioning
confidence: 80%
“…Some of these features have already been experimentally observed in nonlinear left-handed transmission lines which are model systems allowing for combining nonlinearity and anomalous dispersion [17,18,19]. Moreover, first results on harmonic generation in infrared were reported in Ref.…”
mentioning
confidence: 80%
“…In recent years, tunable metamaterials have attracted intensive attentions due to their particular applications in optical switching, nonlinear modulation, and so on [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. The common mechanism is to introduce certain controllable materials or lumped elements into the metamaterial units.…”
Section: Introductionmentioning
confidence: 99%
“…People also find in the transmission line metamaterials, varactor diodes can give rise to the tunability as they are very sensitive to a low direct current voltage, for instance, leaky-wave antenna with tunable radiation angle and beamwidth, tuneable directional coupler, and so on [51][52][53][54][55]. Specifically, transmission line metamaterials with varactor diodes can even serve as model systems for investigating several nonlinear phenomena in negative-index metamaterials, like asymmetric parametric amplification, abnormal pulse formation, dark schrodinger solitons and harmonic generation [56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…III) we use a value for the initial voltage equal to V 0 = 0.5 V (in physical units). For such a value of the voltage (similar, and even smaller, values have also been used in relevant experimental works [29][30][31][32][33][34]), it can be found that…”
Section: A the Nonlinear Lattice Modelmentioning
confidence: 89%
“…In the results below, we have fixed the parameters related to the soliton's amplitude as η = 1 and ε = 0.02, which correspond to an initial value of the voltage equal to V 0 = 0.5 V (similar, and even smaller, values have also been used in experiments [29][30][31][32][33][34]). Furthermore, we have fixed the initial soliton position to X 0 (0) = 1/2, and we have varied the frequency f and the soliton wave number K (recall that the latter sets the initial soliton momentum).…”
Section: A Analysis Of the "Regular" Srr-cpw Structurementioning
confidence: 99%